High Self-Efficacy Strongly Predicted Self-Management Among Hypertensive Patients in Palembang - Sanny Frisca; Dheni Koerniawan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hypertension as a chronic disease with a major sign of increased blood pressure is becoming a problem globally. Increased blood pressure can be the cause of various other chronic diseases such as coronary artery disease and stroke. As an effort to prevent these complications, hypertensive patients need good and sustainable self-care. Self-efficacy is one of the factors that contribute to good self-care. This study aims to determine the effectiveness of self-efficacy on self-management in hypertensive patients. This study was conducted in Palembang with 35 respondents with hypertension aged >17 years. Data was taken through self-efficacy and self-management questionnaires that have been declared valid and reliable. Most 35 respondents have elementary and high-school education backgrounds, high self-efficacy, and moderate self-management. Self-efficacy strongly predicts self-management, although age and educational background do not significantly influence it.